Interpretative phenomenological analysis : theory, method and research - Smith, Jonathan A.; Flowers, Paul.; Larkin, Michael, 1971- (Los Angeles : SAGE, 2009)
This title presents a comprehensive guide to interpretative phenomenological analysis (IPA) which is an increasingly popular approach to qualitative inquiry taught to undergraduate and postgraduate students today.
Includes bibliographical references (p. [207]-217) and index.
Keywords: Phenomenological psychology; Psychology -- Research